Paintless Dent Repair (Pdr) Technology: Operational, Economic, And Environmental Aspects of Implementation in The Auto Body Repair System - Davydenko, Oleksandr (The American Journal of Engineering and Technology, 2026)
Paintless Dent Repair (PDR) technology represents a modern method for restoring vehicle body panels without damaging the original paint coating. In the context of a growing vehicle fleet, increasingly stringent environmental regulations, and rising costs of conventional body repair, the search for resource-efficient and economically viable repair technologies has become particularly relevant. The aim of this study is to provide a comprehensive analysis of PDR technology as an element of the contemporary body repair system from the perspectives of operational efficiency, economic feasibility, and environmental sustainability. The research employs methods of comparative analysis of conventional and paintless repair technologies, techno-economic assessment of production processes, and synthesis of professional practice data from service centers and insurance organizations. The key technological features of PDR, equipment and personnel qualification requirements, as well as the limitations of the method’s applicability are examined. Based on the analysis of 124 repair cases (62 PDR and 62 conventional repairs), it was found that the average repair time decreased from 9.4 ± 1.8 hours to 1.7 ± 0.6 hours, while the average cost was reduced from 470 to 185 USD. The annual economic effect at a workload of 35 orders per month amounted to 119,700 USD. The elimination of painting operations made it possible to prevent up to 60.9 kg of volatile organic compound (VOC) emissions per year. The study concludes that integrating PDR technology into modern body repair systems is justified as a sustainable and promising direction that meets economic, environmental, and service quality requirements.